Leaf area, chlorophyll content, and relative growth rate of grass on different shading and fertilization - Sirait, Juniar (Indonesian Animal Sciences Society, 2008)
Plant morphology and physiology such as leaf area, total chlorophyll, and chlorophyll a/b ratio were affected by shading and fertilization. An experiment was conducted in Indonesian Research Institute for Animal Production (IRIAP) Ciawi, West Java. The objective of this study was to determine the morphology and physiology adaptation of three short grasses species for grazing namely Paspalum notatum, Brachiaria humidicola, Stenotaphrum secundatum on different shading and fertilization level. The experiment was arranged in split-split plot design. The main plot was shading level (0, 38, 56%); sub-plot was fertilizer dosage (0, 100, and 200 kg N/ha) while sub-sub plot was grass species. The results showed that leaf area were significantly different on different grass species, and there was interaction between shading and species on total leaf area. P. notatum on 38% shading level has the highest total leaf area (240.2 cm2). S. secundatum and P. notatum had a better adaptation in shading area compared to B. humidicola by increasing of total chlorophyll and decreasing of chlorophyll a/b ratio. Relative growth rate (RGR) of P. notatum and S. secundatum were increased by the increasing shading level. On the other hand relative growth rate of B. humidicola was decreased by the increasingÂ shading level. Leaf area, chlorophyll content, and RGR were not significantly affected by fertilization dosage. Key Words: Shading, Fertilization, Adaptation, Growth, Chlorophyll